Amarna Glosses - Moran, William L.
ersch. 1976; The Sin of Lab’ayu, EA 253f. (irony, not confession); Life from the Pharaoh, EA 369:21 (read pī ši-pir6-ti, not ka-ši NAM.TI);Ba‛lu-šipṭi of Gezer, EA 292f. (mdIM.DI.KUD = Addu-dāni, not Ba‛lu-šipṭi); The Investiture of the Commissioner, EA 107:20ff. (read MAŠKIM-ši DUGUD, not MAŠKIM ši-mi-rum); The Siege of Byblos, EA 88:21 (read EDIN, not am-ru); UŠ ú-ṣa, EA 101:10 (read rather GÚ.UN).